Peranan Bahasa Inggris Komunikatif dalam Meningkatkan Pelayanan Anggota Kepolisian Sektor Denpasar Selatan - I Nyoman Muliana; I Made Astu Mahayana (Warmadewa Press, 2020)
The problem faced by members of South Denpasar Police Sector as community service partners is their very limited ability to communicate in English, such as asking questions and giving explanations when providing services to foreigners. This study aims to determine the role of communicative English in improving services for members of South Denpasar Sector Police. The method used in this study is a lecture, pair work, and conversation methods. This study was conducted at South Denpasar Sector Police Office. The office is located in the tourist area of ​​Sanur, so automatically the area of ​​duty includes Sanur area itself, which is one of the main tourist destinations for domestic and foreign tourists. The results of this study indicated that communicative English training can have an impact on vocabulary mastery, communication skills, and grammar mastery by the trainees.